Effect of polepiece geometry on objective snorkel lens properties - Al-Salih, R. Y. J.; Kalil, Nawras K. (AIP conference proceedings, 2024)
The shape of the polepiece area greatly influences the performance of the magnetic objective lens. A novel design for a (Snorkel Lens) with particular geometric dimensions and a square polepiece form was produced, in the current study different polepiece forms were created called [P1, P2, P3, P4, and P5] and the influence of the geometry of the pole on the objective characteristics of the lens was explored while the lens’s other geometric parameters remained constant. The results showed that the lens with the pole form [P2] has the best resolution.